The Research on the Professional Development of Middle School Mathematics Teachers Based on Core Quality - Yang, Zezhong; An, Liping; Lu, Ruixue; Fan, Siqi (American Journal of Education and Learning, 2018)
The core quality of the discipline and the core quality of students is the new direction of Chinese education reform. However, the development of the core quality of the discipline and the cultivation of students’ core quality are inseparable from the effective guidance of teachers. Therefore, it is important for teachers to obtain corresponding professional development. Based on the needs of social development, this paper started from the connotation of core quality and the professional development of middle school teachers, and discussed the consciousness, knowledge and ability of middle school mathematics teachers in detail.